How Can Individual Self-Studies Contribute to a Web of Betweeness? How Can I Become We Without Losing I? - Farren, Margaret; Power, Darragh (Proceedings of the International Conference on Networked Learning, 2004)
Information and Communications technology (ICT) has assumed an increasingly important role in society, in the way people communicate with each other, and do business. It would seem logical that educational providers take account of technological developments as they seek to develop teaching and learning. If ICT is to play an effective role in professional development of teachers certain needs must be addressed over and above the provision of ICT training. This paper will show how these needs have been addressed in the context of the professional development of teachers on a Masters in Education and Training (ICT). Some of these needs include: developing a greater awareness of the potential of ICT as a tool and as a medium to support teaching and learning; developing new and appropriate knowledge and skills in using ICT in teaching and learning; developing a greater awareness of the ways ICT affects the ways we think about, organize and practice teaching and learning.